The fairy swarm - Selfors, Suzanne (Little, Brown and Company, 2015)
"Ten-year-olds Ben Silverstein and Pearl Petal have had quite a busy summer as apprentices of Dr. Woo, veterinarian for imaginary creatures. When a swarm of sugar fairies escapes into Buttonville, Ben and Pearl must protect the townspeople, keep the fairies safe, and outsmart the dangerous poacher, Maximus Steele"...
Keywords: JUVENILE FICTION / Animals / Mythical / bisacsh; JUVENILE FICTION / Fantasy & Magic / bisacsh; JUVENILE FICTION / Action & Adventure / General / bisacsh; JUVENILE FICTION / Mysteries & Detective Stories / bisacsh; JUVENILE FICTION / Social Issues / Friendship / bisacsh; Fairies; Imaginary creatures; Veterinarians; Apprentices; JUVENILE FICTION / Animals / Mythical; JUVENILE FICTION / Fantasy & Magic; JUVENILE FICTION / Action & Adventure / General; JUVENILE FICTION / Mysteries & Detective Stories; JUVENILE FICTION / Social Issues / Friendship; Jugendbuch